PENGEMBANGAN KECERDASAN SPIRITUAL SISWA DI SD ISLAM TOMPOKERSAN LUMAJANG - Lufiana Harnani Utami (Psympathic : Jurnal Ilmiah Psikologi, 2015)
Spiritual quotient function transforming spiritual values such as honesty, affection, fairness, responsibility, peacefulness, trust, and togetherness. Developing Spiritual quotient aims to make students have full understanding about lesson of Islam and be able to apply it in daily life. Students hoped to be the one who believe in Allah SWT and actualize themselves based on lesson and norm in Islam with Islamic personality and akhlakul karimah. This research uses qualitative approach by having interview with subjects. Result shows that spiritual quotient development is carried through structural and unstructural programs. Structural programs applied in learning activity while unstructural ones done through extracuriculer activites. Methods of development are giving assignment, nurturing, transforming knowledge, having creative activity, making relationship having leadership.